2019
DOI: 10.1016/j.ijfatigue.2019.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Mixed mode I/II fatigue crack arrest in steel members using prestressed CFRP reinforcement

Abstract: In the present study, a strengthening design approach is proposed for the mixed mode I/II fatigue crack arrest in existing structural steel members using prestressed unbonded carbon fiber reinforced polymer (CFRP) composites. Through the analytical formulation of mode I and II stress intensity factor ranges, a design model is proposed to determine the strengthening solution, including the required prestressing level and/or the cross-sectional area of the reinforcement, which would ensure the complete arrest of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 54 publications
0
4
1
Order By: Relevance
“…Note that the above results were not confirmed by the experimental study in [18] where it was shown that the mode mixity also plays a role on the fatigue lifetime. Fatigue crack growth in CFRP repaired four-point bend specimens was investigated in [10].…”
Section: State-of-the-art Studiescontrasting
confidence: 61%
See 1 more Smart Citation
“…Note that the above results were not confirmed by the experimental study in [18] where it was shown that the mode mixity also plays a role on the fatigue lifetime. Fatigue crack growth in CFRP repaired four-point bend specimens was investigated in [10].…”
Section: State-of-the-art Studiescontrasting
confidence: 61%
“…This technique was successfully applied to strengthen old steel bridges in Switzerland [3] and in Australia [4]. In all the above-mentioned studies, emphasis was on preventing crack initiation or on promoting crack arrest under both mode I [17] and mixed mode I/II [18] loading condition, resulting in the fatigue lifetime extension of old fatigue-sensitive steel structures. They proposed, through some conservative assumptions, suitable models to achieve a practical estimation of the fatigue crack threshold and the required prestressing level in the strengthening systems for crack arrest.…”
Section: State-of-the-art Studiesmentioning
confidence: 99%
“…Nevertheless, with some further crack propagation and with the presence of shear stresses, the combined effects of bending and shear stresses govern the crack scenario. However, the mechanisms for crack propagation is still based on maximum principal stress [58]. The fatigue crack growth is resolved by the mode-I stress intensity factor (SIF) range, ∆K I = K I,max − K I,min , at the tip of the crack during the early stages of propagation.…”
Section: Fe Simulationmentioning
confidence: 99%
“…Adding pre-stressing force in the CFRP material allows using a more significant portion of the strength of the material. Moreover, by applying an adequate level of pre-stress to the CFRP laminate, the effective SIF at crack tip can be reduced below the SIF threshold and therefore lead to a full stop of the crack propagation [ 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%